Politologija, znanost, psihoanaliza, resnica - Balažic, Milan (Teorija in praksa, 2000)
Scientific discourse is formed like paranoya. Inhibition and silence of God is talking through scientific writing. In principle, subject of science is eliminated and only with expirience of 'manque in Autre', science reaches post-phantasmatic relation to its object. Political sciences appear like utilitarian knowledge, the way of existence of theory in a capitalistic society. With inscription of subject, the aim of psychoanalysis is truth, although it can itself convert to the Master's therapy of conformity. The field of political sciences as historical knowledge is political reality, and the field of psychoanalysis as "unhistorical" is the logic of unconsciousness. From the link of knowledge and truth the revolutions arise.
Keywords: politologija; psihoanaliza; kritična teorija družbe; znanstveni diskurz